Potential Analysis of Hydro Power Plants in Pesisir Barat District, Lampung Province - Kiki Kananda; Dean Corio; Hafif Restu K.; Hilmi Aziz; Topan Wira B.; Diah A. (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2019)
Hydropower plants are increasingly being heard nowadays, but the growth is still very lacking, especially for residents living in rural and coastal areas. At present several efforts have been made by the government, including the existence of a system of purchasing electricity from small-scale renewable energy generation and the construction of new transmission networks. Pesisir Barat Regency is part of the South Lampung region, Sumatra. This region has a population distribution in the coastal area and is surrounded by Bukit Barisan National Park. So that there are many large river streams that can be utilized by the local community. Large rivers have the potential to be utilized further as hydropower renewable energy sources. River potential is seen by conducting river location surveys, flow measurements and river heads and power calculations. Based on the analysis of measurement results there are two rivers that have the potential to be a micro or mini hydro generator; Way Laai and Way Lami. The maximum design discharge of Way Laai of 4.52 m3/s can produce a mechanical output power of 1223.82 kW with an effective head of 44.16 m. Way Lami with a design discharge of 5,336 m3/s, an effective head of 28.8 m has the potential to provide a mechanical power output of 942.23 kW. Sequentially, with this mechanical output power, the Way Laai and Way Lami rivers, can meet the electricity needs of the community with an installed power of 900VA as much as Â± 1350, Â± 25100 Houses.